Psoroptes ovis‐Early Immunoreactive Protein (Pso‐EIP‐1) a novel diagnostic antigen for sheep scab. (14th September 2020) - Burgess, Stewart T. G.; Nunn, Francesca; Bartley, Kath; Frew, David; McLean, Kevin; Inglis, Neil F.; McGeachy, Kara; Taliansky, Michael E.; Love, Andrew J.; Nisbet, Andrew J.
Abstract: Aims: Serodiagnosis of sheep scab is an established diagnostic method and has become popular in recent years. However, the current diagnostic antigen, Pso o 2, has shown promise as a component of a recombinant vaccine for scab, making it incompatible with discriminating between infected and vaccinated animals (DIVA). Here, we describe the discovery and characterization of a novel Psoroptes ovis immunodiagnostic antigen, P. ovis ‐Early Immunoreactive Protein‐1 (Pso‐EIP‐1). Methods and Results: Pso‐EIP‐1 is a highly abundant member of a six‐gene family with no known homologs, indicating its potential uniqueness to P. ovis . Expression of recombinant Pso‐EIP‐1 (rPso‐EIP‐1) required a C‐terminal fusion protein for stability and specific IgG immunoreactivity against rPso‐EIP‐1 was observed in sheep serum from 1 to 2 weeks post‐infestation, indicating its highly immunogenic nature. Two of the three in silico‐predicted B‐cell epitopes of Pso‐EIP‐1 were confirmed by in vitro epitope mapping and, in a direct comparison by ELISA, Pso‐EIP‐1 performed to the same levels as Pso o 2 in terms of sensitivity, specificity and ability to diagnose P. ovis on sheep within 2 weeks of infestation. Conclusion: Pso‐EIP‐1 represents a novel diagnostic antigen for sheep scab with comparable levels of sensitivity and specificity to the existing Pso o 2 antigen.